Streptolysin O Inhibits Clathrin-Dependent Internalization of Group A Streptococcus - Lauren K. Logsdon (American Society for Microbiology, 2011)
ABSTRACT Group A Streptococcus (GAS) can be internalized by epithelial cells, including keratinocytes from human skin or pharyngeal epithelium. Internalization of GAS by epithelial cells has been postulated both to play a role in host defense and to provide a sanctuary site for GAS survival. The cholesterol-binding cytolysin streptolysin O (SLO) appears to enhance virulence in part by inhibiting GAS internalization by human keratinocytes and by disrupting the lysosomal degradation of internalized GAS. We now report that low-level production of SLO by an inducible expression system reduced GAS internalization by keratinocytes. Induced SLO expression also prevented lysosomal colocalization with intracellular bacteria and acidification of GAS-containing vacuoles. Exogenous recombinant SLO mimicked the inhibitory effect of SLO secretion on GAS entry but not that on colocalization with the lysosomal marker LAMP-1, implying that disruption of lysosomal degradation requires intracellular secretion of SLO. The internalization of SLO-negative GAS was blocked by the depletion of host cell cholesterol and by the inhibition or knocking down of the expression of clathrin or dynamin. SLO also inhibited the cellular uptake of other cargos that are internalized by clathrin-mediated uptake or by macropinocytosis. We conclude that SLO interferes with the internalization of GAS through local perturbation of the keratinocyte cell membrane and disruption of a clathrin-dependent uptake pathway. IMPORTANCE Streptolysin O (SLO) is a member of a family of pore-forming toxins, the cholesterol-dependent cytolysins, that are produced by many Gram-positive bacterial pathogens. While SLO can lyse host cells at high doses, much smaller amounts appear to contribute to pathogenesis by inhibiting the internalization of group A Streptococcus (GAS) by pharyngeal keratinocytes and by preventing efficient intracellular killing by lysosomal fusion. This study provides evidence that SLO blocks a clathrin-dependent pathway for the internalization of GAS through effects on the cell surface, whereas inhibition of lysosomal fusion depends on the intracellular production of SLO. These observations may have broader implications for understanding the pathogenesis of multiple bacterial species that produce cholesterol-dependent cytolysins.